Pengembangan Aplikasi Penyimak Al-Qur’an Menggunakan Teknologi AI dengan Metode Speech Recognition pada Platform Android - Hudayana, Nur Alawi; Haris, Abdul; Zakaria, Azril Rakhmat (Journal of Islamic Education, 2024)
This study aims to develop an application for learning to read the Qur'an based on artificial intelligence (AI) with a speech recognition method on the Android platform and evaluate the user experience. This study uses the Rapid Application Development (RAD) method with the stages of needs analysis, design, implementation, and testing. This application has the main features of verse search, voice detection, and surah selection. The results of the performance test show that the application is able to detect and transcribe short verses of the Qur'an, although it has not been able to detect and transcribe long verses of the Qur'an. The feasibility test produced a score of 92.50% which shows that the application is very feasible to use where all application buttons function as expected. This application is expected to help Muslims in reading and memorizing the Qur'an, while overcoming the limitations of traditional learning methods by offering more interactive and personal learning methods.